GENETIC ANALYSIS OF YIELD AND ITS ATTRIBUTES IN RICE (Oryza sativa L.) - CH. SREELAKSHMI*; P. RAMESH BABU (The Journal of Research ANGRAU, 2020)
The experiment (2014-16) was conducted to study the genetic parameters for yield and its contributing traits revealed that number of unfilled grains/ panicle, 1000 grain weight and grain yield recorded high PCV and GCV values. High heritability with high GA as% of mean (genetic advance as percent of mean) was observed for effective bearing tillers per plant, number of filled grains/panicle, number of unfilled grains per panicle, 1000 seed weight and grain yield indicating the involvement of additive gene action in the inheritance of the traits hence it is sufficient to follow simple selection. A light on correlation studies revealed that positive direct effect of grain yield was observed with number of ear bearing tillers per plant, number of filled grains/ panicle, harvest index, days taken for 50% flowering and days taken for maturity and selection may be effective based on these traits to isolate high yielding genotypes. Path coefficient analysis revealed that, days taken for maturity, number of ear bearing tillers/plant, number of filled grains/ panicle and harvest index had shown high positive direct effect as well as positive association with grain yield. Hence, the above traits may be considered as an important criterion in the rice improvement programme